Professionalism of Nurses Performing Humanitarian Duties During a Pandemic - Dewi Setya Paramitha (Malahayati Nursing Journal, 2023)
ABSTRACT There are many stories of COVID-19 nurses who express feelings of anxiety, fear of being infected and infecting loved ones. This feeling makes their struggle hard in providing nursing care. They have to fight the fear of being infected. This study explored how nurses struggle to harmonize professional obligations with the instinct to protect their own safety. The research design used a qualitative method with a phenomenological approach. The participants ware COVID-19 nurses at the Banjarmasin Private Hospital taken by simple random sampling. The results of the study obtained five themes, namely the mechanism for placing nurses in the COVID-19 ward, the perception of nurses when assigned to the COVID-19 ward, the expectations desired by nurses, the response of the family members of COVID-19 nurses and the positive impact pandemic for nurses. Even though every nurse’s experiences various stressors, in the end they still show their commitment as health workers. have an adequate support both from hospital setting or their families. Their realize that their duties not only for patient recovery but also for the better life of community. Keywords: COVID-19, Nursing care, Professionalism, Stressor, Support system        ABSTRAK Banyak kisah perawat COVID-19 yang mengungkapkan perasaan cemas, takut tertular dan menulari orang yang disayang. Perasaan ini membuat perjuangan mereka berat dalam memberikan asuhan keperawatan. Mereka harus melawan rasa takut terinfeksi. Penelitian ini mengeksplorasi bagaimana perawat berjuang untuk menyelaraskan kewajiban profesional dengan naluri untuk melindungi keselamatan mereka sendiri. Desain penelitian menggunakan metode kualitatif dengan pendekatan fenomenologis. Partisipan perawat COVID-19 di RS Swasta Banjarmasin diambil secara simple random sampling. Hasil penelitian didapatkan lima tema yaitu mekanisme penempatan perawat di bangsal COVID-19, persepsi perawat saat ditugaskan di bangsal COVID-19, harapan yang diinginkan perawat, respon anggota keluarga COVID-19 perawat dan pandemi dampak positif bagi perawat. Meskipun setiap perawat mengalami berbagai stressor, pada akhirnya mereka tetap menunjukkan komitmennya sebagai tenaga kesehatan. Perawat memiliki dukungan yang memadai baik dari lingkungan rumah sakit maupun keluarganya. Mereka menyadari bahwa tugasnya tidak hanya untuk kesembuhan pasien tetapi juga untuk kehidupan masyarakat yang lebih baik. Kata Kunci: Asuhan Keperawatan, COVID-19, Profesionalisme, Stressor, Support System